United States. Army payroll receipts - United States. Army.
Transcript of payroll receipts (1814 September 9-December 31) for American soldiers incarcerated at Chatham and Dartmoor, England, during the War of 1812. Lists name, rank, regiment, and amount received. Apparently kept by Reuben Gaunt Beasley, American agent in Great Britain.
Typewritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Formerly part of United States Army miscellany collection.
Keywords: Beasley, Reuben Gaunt; United States. -- Army -- Pay, allowances, etc; Chatham (Kent, England) -- History; Dartmoor (England) -- History; United States -- History -- War of 1812 -- Prisoners and prisons, British